Influence of Lithosphere Rheology on Seismicity in an Intracontinental Rift: The Case of the Rhine Graben - Anikiev, Denis; Cacace, Mauro; Bott, Judith; Gomez Dacal, Maria Laura; Scheck-Wenderoth, Magdalena (Frontiers in Earth Science, 2020)
The Upper Rhine Graben (URG), as a part of the wider European Cenozoic Rift System, is a tectonically active area that has been extensively investigated for its geothermal energy potential. In this study, we carry out a first investigation of the present-day thermo-mechanical stability of the area as based on a detailed 3D geological and thermal model. The overall goal is, therefore, to assess how the lithospheric strength varies within the URG in response to the natural tectonic setting as well as the internal thermal configuration, and how those variations can be related to the recorded seismicity. The results from the modelling indicate that there is a spatial correlation between the predictions for the graben-wide rheological configuration with both the deep thermal field and the configuration of the crystalline crust. We find that the regional characteristics of the long-term strength of the lithosphere match the spatial distribution of seismicity, indicating that the mechanical stability of the area is primarily controlled by resolved strength variations. By cross-plotting the modelled strength distribution with available seismicity catalogues, our results suggest that seismicity in the graben area is shallower and of lower intensity due to a hotter and weaker crust compared to its surrounding areas. In contrast, seismic energy release appears to occur at deeper levels and being of larger magnitudes east of the graben and in the adjacent Lower Rhine Graben to the north. These results demonstrate the relevance of a proper quantification of the lithospheric rheological configuration and its spatial variability in response to its tectonic inheritance as an asset to interpret the pattern and distribution of seismicity observed in the area.